Normal Iron Homeostasis Requires the Transporter SLC48A1 for Efficient Heme-Iron Recycling in Mammals - Simmons, William R.; Wain, Lily; Toker, Joseph; Jagadeesh, Jaya; Garrett, Lisa J.; Pek, Rini H.; Hamza, Iqbal; Bodine, David M. (Frontiers in Genome Editing, 2020)
In mammals over 65% of the total body iron is located within erythrocytes in the heme moieties of hemoglobin. Iron homeostasis requires iron absorbed from the diet by the gut as well as recycling of iron after the destruction of senescent erythrocytes. Senescent erythrocytes are engulfed by reticuloendothelial system macrophages where hemoglobin is broken down in the lysosomes, releasing heme for iron recovery in the cytoplasm. We recently showed that the SLC48A1 protein is responsible for transporting heme from the lysosome to the cytoplasm. CRISPR generated SLC48A1-deficient mice accumulate heme in their reticuloendothelial system macrophages as hemozoin crystals. Here we describe additional features of SLC48A1-deficient mice. We show that visible hemozoin first appears in the reticuloendothelial system macrophages of SLC48A1-deficient mice at 8 days of age, indicating the onset of erythrocyte recycling. Evaluation of normal and SLC48A1-deficient mice on iron-controlled diets show that SLC48A1-mediated iron recycling is equivalent to at least 10 parts per million of dietary iron. We propose that mutations in human SLC48A1 could contribute to idiopathic iron disorders.